Influence of Self-Motivation and Health Locus of Control on Adherence to Medication Among Hypertension Patients - Nur Ainiyah; Najmiatu Zuhriyah; Chilyatiz Zahroh; Siti Damawiyah; Diah Retno Kusumawati; R. Khairiyatul Afiyah; Syiddatul Budury; Andikawati Fitriasari (Fakultas Ilmu Keperawatan Universitas Indonesia, 2023)
Hypertension is one of the more common comorbidities among patients infected with the Sars-CoV-2 virus, which causes COVID-19, but many hypertensive patients do not comply with taking medication. This study analyzed the relationship of self-motivation and health locus of control with self-management (medication adherence) among hypertensive patients during the COVID-19 pandemic at Private Hospital Surabaya, Indonesia. The research adopted a correlative analytic design with a cross-sectional approach, and the study’s population comprised 74 hypertensive patients recruited by simple random sampling who were treated at Private Hospital Surabaya, Indonesia The instruments used included the Treatment Self-Regulation Questionnaire to measure self-motivation, the Multidimensional Health Locus of Control Scale to measure locus of control, and the Morisky Medication Adherence Scale–8 to measure self-management (medication adherence). Spearman’s rank correlation coefficient was employed for data analysis to measure the relationships between self-motivation, locus of control, and with self-management (adherence to taking medication). The results reveal a relationship between self-motivation and adherence to medication at a level of p = 0.000 and a relationship between health locus of control and adherence to taking medication at a level of p = 0.000 among hypertensive patients during the COVID-19 pandemic at Private Hospital Surabaya, Indonesia. The findings suggest the value of efforts to provide motivation to patients and support their being more responsible in controlling their health conditions by adherence to medication. Abstrak Pengaruh Motivasi Diri dan Locus of Control pada Kepatuhan Minum Obat Pasien dengan Hipertensi. Hipertensi merupakan salah satu penyakit dengan komorbiditas tertinggi pada pasien yang terinfeksi virus Sars-CoV-2 penyebab COVID-19, diperparah dengan masih banyaknya pasien hipertensi yang tidak patuh minum obat. Penelitian ini bertujuan untuk menganalisis hubungan motivasi diri dan health locus of control dengan self-management (kepatuhan minum obat) pada pasien hipertensi pada era pandemi COVID-19 di rumah sakit swasta Surabaya. Desain penelitian ini adalah analitik korelatif dengan pendekatan cross-sectional. Populasi penelitian ini adalah pasien hipertensi yang dirawat di rumah sakit swasta Surabaya Indonesia dengan simple random sampling sebanyak 74 orang. Instrumen yang digunakan dalam penelitian ini adalah the Treatment Self-Regulation Questionnaire untuk mengukur motivasi diri, Multidimensional Health Locus of Control Scale untuk mengukur locus of control, dan Morisky, Medication Adherence Scale untuk mengukur selfmanagement (kepatuhan pengobatan). Analisis data yang digunakan untuk mengukur self-motivation, locus of control dengan self-management (kepatuhan minum obat) adalah tes Rank Spearman. Hasil penelitian menunjukkan bahwa ada hubungan antara motivasi diri dengan kepatuhan minum obat pada pasien hipertensi di era pandemi COVID-19 di rumah sakit swasta Surabaya dengan taraf (p = 0,000), dan ada hubungan antara lokus kesehatan dengan pengendalian dan kepatuhan minum obat bagi pasien hipertensi di era pandemi COVID-19 di rumah sakit swasta Surabaya (p = 0,000). Hasil penelitian menunjukkan bahwa upaya dengan memberikan motivasi dan dukungan untuk lebih bertanggung jawab dalam mengontrol kondisi kesehatannya (patuh minum obat). Kata Kunci: kepatuhan minum obat, locus of control, pasien hipertensi, self-motivation